2011
DOI: 10.1007/s00204-011-0760-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms of EPHX1 and XRCC1 genes and the risk of childhood acute lymphoblastic leukemia

Abstract: Microsomal epoxide hydrolase, EPHX1, plays a central role in the detoxification of potentially genotoxic epoxide intermediates. In this study, we firstly aimed to investigate the relationship between EPHX1 Tyr113His and His139Arg variants, and the risk of incidence of childhood acute lymphoblastic leukemia (ALL) in Turkish population, comprised of 190 healthy controls and 167 ALL patients. In exon 3 Tyr113His polymorphism, 113His/His homozygous mutant genotype with slow activity was 18.6% in ALL patients and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
2
17
2
Order By: Relevance
“…Tumer et al reported that only the very low activity of the 113 His/His and 139 His/His combinations significantly increased the risk of childhood ALL [21]. However, in our study, no associations were found between these combinations and childhood ALL.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Tumer et al reported that only the very low activity of the 113 His/His and 139 His/His combinations significantly increased the risk of childhood ALL [21]. However, in our study, no associations were found between these combinations and childhood ALL.…”
Section: Discussioncontrasting
confidence: 88%
“…Three studies of childhood ALL risk have also reported no association with His139Arg, while Tyr113His showed a decreased risk [7] in Brazil, an increase [21] in Turkey, and no association [11] in France. Our results are similar to those of Silveira Vda et al [7].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, the data showed that EPHX1 gene expression in de novo patients is much higher than control group (P=0.0376). However, what many reports shown was that the EPHX1 gene polymorphisms play an important role in both the activation and detoxification of carcinogenic PAHs and aromatic amines [9][10][11]. Chemotherapeutics (daunorubicin, cytarabine, et.al) which are used for cancer patients almostly based on PAHs, which are also carcinogens in essence.…”
Section: Discussionmentioning
confidence: 99%
“…Acrylamide compromises progenitor cells in the hippocampal dentate gyrus of rats Ogawa et al (2012) DMSO induces phenotypic alterations and massive alterations in gene expression in stem cells Pal et al (2012) The phytochemical glucoraphasatin induces hepatic phase II metabolizing enzymes Razis et al (2012) The herbicide glyphosate causes DNA strand breaks and micronuclei in vitro Koller et al (2012) Cadmium modulates Ah receptor expression in the rat uterus via the estrogen receptor Kluxen et al (2012) A predictive in silico tool for prediction of human bioaccumulation was established Tonnelier et al (2012) The microsomal epoxide hydrolase variant 113 His/His reduces detoxification of carcinogenic epoxides Tumer et al (2012) UDP GT 1A1 is the principle enzyme for puerarin conjugation in human liver Luo et al (2012) Estragole, an organic compound used as a food additive, may be a genotoxic hepato-carcinogen Suzuki et al (2012) The copper-based drug Casiopeina II-gly simultaneously inhibits oxidative phosphorylation and glycolysis Marin-Hernandez et al (2012) The mycotoxins alternariol and alternariol methyl ether induce CYP1A1 in an Ah receptor-dependent manner Schreck et al (2012) Perfluorooctane sulfonate acts as a non-genotoxic carcinogen Jacquet et al (2012) A low scaling factor for human inter-individual differences in formaldehyde-induced genotoxicity is recommended Zeller et al (2012) Variants of superoxide dismutase and 8-oxoguanine DNA glycosylase conferred increased risk of hypertension when associated with arsenic exposure Chen et al (2012) …”
Section: Escobar-garcia Et Al (2012)mentioning
confidence: 99%